Final Report of the Internal Reorganisation Committee - Planning Commission (Planning Commission, 1971)
The Internal Reorganisation Committee submitted its Interim Report in February, 1963, This, the Final Report, has to be read with the Interim Report.
Government of India Planning Commission
Government of India Planning Commission